The Suicide Behaviours Questionnaire dan Brief Symptom Inventory: Validasi Skala Kontekstual pada Mahasiswa di Indonesia - Setyaningtyas, Angelina Dyah Arum; Anggraeni, Dewi Soerna; Rahmawan, Ridwan (Arus Jurnal Pendidikan, 2026)
This study aims to validate the Suicide Behaviors Questionnaire-Revised (SBQ-R) and the Brief Symptom Inventory (BSI) in the context of Indonesian university students. A quantitative approach with a cross-sectional survey design was employed. Participants consisted of 365 active students aged 18–25 years, selected through purposive sampling. The validity and reliability of both instruments were examined using Cronbach's alpha analysis, inter-item correlations, and group difference tests. Results indicated that SBQ-R demonstrated high reliability (α = 0.834) for assessing suicide risk, while BSI showed very high reliability (α = 0.973) in evaluating psychological distress. These findings confirm that both instruments are valid and reliable tools for Indonesia's cultural context. This study contributes significantly to the development of evidence-based screening tools for preventing suicide risk and psychological distress among students, emphasizing the importance of culturally sensitive approaches in mental health interventions.